Spatio-time psychomotor references of motor characteristics in volleyball - Rzhanov, A. A.; Akhmatgatin, A. A.; Lebedinsky, V. Yu.; Kharkovskaya, A. G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determination of the significance and interpretation of the influence of psychomotor spatio-temporal characteristics of volleyball players on the game process, search for ways and methods to effectively form and develop these abilities.